Testosterone secreting adrenal adenoma in an adult female patient - Alam, MM; Rahman, MA; Naser, MF; Hossain, MS; Islam, MA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):632-5 The abstract of this article is available on the PubMed website